RANCANG BANGUN APLIKASI MATEMATIKA UNTUK SISWA SD KELAS 4 MENGGUNAKAN BAHASA PEMROGRAMAN JAVA BERBASIS ANDROID - Kristina, Kristina; Widjana, Lilyana; Apriani, Vera (INTEKSIS, 2024)
The world of education must adapt to computer technology developments to provide more optimal results. The ability to adapt to the world of education in computer technology can be achieved by implementing computerization in the learning system. The implementation is by building a learning application that contains unique material for each level of education. The research method used is the descriptive research method. The data collection techniques used were literature study, observation, and interviews. The data used is mathematics lesson data for grade 4 elementary school (SD) students. The research problem raised is how to design an Android-based mathematics application that is practical and easy to use. The solution that will be implemented in this research is to develop a mathematics application aimed at grade 4 elementary school students. Mathematics applications are created interactively to make learning mathematics easier and more comfortable. This application contains material regarding 4th-grade elementary school mathematics, exercises, and quizzes to determine how much children understand while studying. This application is also equipped with practice questions so that children can do the exercises given after studying the material provided in this application. This article aims to show a report on the results of creating a mathematics application called "MathIsFun." This mathematics application was developed in Android Studio with Firebase as user data collection. The Firebase used is Firebase Authentication and Firebase Realtime Database. Firebase Authentication makes it easy for users to log in to applications. Firebase Realtime Database synchronizes data in realtime for each connected user. Android Studio is an application used to develop Android applications. Keywords: Learning Application, Mathematics, Android Studio, Elementary School